Evaluating a Statewide OER Repository on the Hyku Platform - Bryan McGeary (Journal of New Librarianship)
As the number of open educational resources (OER) has rapidly grown in recent years, a variety of repositories and referatories have been developed to facilitate discovery and usage of them. This article details the results of a pilot study to determine the suitability of Hyku as a statewide repository platform for OER materials and the viability of running such a service long-term in Pennsylvania. Study participants deposited materials in the repository and provided feedback aimed at understanding its value to key stakeholders, assessing the usability of the repository for key stakeholders, evaluating the cost of running the repository, and recommending an administrative structure (e.g., centralized or decentralized approach) for supporting and maintaining access to OER via the repository.